(untitled) (Applied Biological Research, 2025)
Isolation of genomic DNA of high quality is a prerequisite for molecular genetic characterisation of any plant. Genomic DNA is usually extracted from plant leaves for downstream applications such as polymerase chain reaction (PCR).Plants have to be grown in fields or pots for leaves. In white Guinea yam (Dioscorea rotundata Poir), raising the plants in fields is a challenging task due to tuber dormancy in many genotypes. DNA can be directly extracted from yam tubers, obviating the need to raise plants in fields. However, high concentrations of secondary metabolites like polyphenols and polysaccharides in yam tubers may affect the genomic DNA extraction.A simple, rapid, inexpensive CTAB-based modified method with high PCR fidelity was standardised for DNA isolation from tubers without using liquid nitrogen. Fresh tubers and tuber samples prepared by alcohol-drying, freezing, and oven-drying were employed for genomic DNA isolation.The quantity, quality, and PCR fidelity of DNA isolated from various methods were verified and compared with the DNA isolated using liquid nitrogen. Alcohol-dried tuber tissues provided consistent, high-quality genomic DNA with absorbance ratio A260/280 of 1.787–1.854 and a concentration of up to 1.8 μg μL⁻¹, with ISSR profile comparable to that of tuber DNA isolated using liquid nitrogen.